Anemia, Chronic Energy Deficiency for Pregnant Women, Non-Exclusive Breastfeeding as Risk Factors for Stunting in Toddlers - Alfatikha, Dhia Naila; Dasuki, Mohammad Shoim (Prosiding University Research Colloquium, 2023)
Stunting is a condition in which a child experiences failure to thrive. WHO data for 2020 the prevalence of stunting is 22%. The latest data from the Ministry of Health states that in 2021 the incidence of stunting in Indonesia will be 24.4%. It is suspected that stunting is caused by several factors, namely history of anemia, nutritional status of pregnant women, breastfeeding, young gestation and hypertension in pregnant women. This study aims to determine the relationship between anemia, chronic energy deficiency (CED) in pregnant women and breastfeeding with the incidence of stunting. This type of research is quantitative observational analytic case control approach. The sample is 156 respondents with details of 78 respondents as the case group and 78 other respondents as the control group. Sampling used secondary data that was collected in the medical records of the Jogorogo Health Center through a purposive sampling technique. The results of the chi-square test showed a relationship between anemia and stunting with a p value <0.001 and an OR of 3.45. The results of the bivariate test showed a correlation between KEK and Stunting with a p value <0.001 and an OR of 2.64. There is a correlation between breastfeeding and the incidence of stunting with a p value <0.001 and OR 3.685. In the logistic regression test, the OR result was 0.128 with a p value <0.001. In conclusion, there is a significant correlation between anemia, CED, and breastfeeding with the incidence of stunting.